Introduction: How do we Understand Working Environment Policies, Programmes and Instruments? - Nielsen, Klaus T.; Hohnen, Pernille (Nordic Journal of Working Life Studies, 2014)
How do different forms of regulation influence working environment and working life? How can centrally formulated programmes create changes at complex, often multi-layered local work places, and how can insights from work life studies shed light on the social mechanisms at stake in different types of regulation? Under the heading of working environment policies, programmes and instruments, the aim of the current issue has been to address these issues. In essences, it is society’s intentional attempt to regulate working environment conditions in the workplace. It could be through health and safety legislation and labour inspection. But it is much more than that: The states are not restricted to writing rules, inspecting and sanctioning them. They put together insurances systems and they support massive campaign efforts. And they get labour market parties, nationally, by the sector or within the companies or workplaces, involved in similar activities; sometimes, labour market parties or other stakeholders even do it without prompts from the state. All these efforts are made to a larger or smaller extent because they are seen as beneficial to the health of the employees. But we know surprisingly little about how policies, programmes and instruments work, the social processes at stake, to what extent they do work and whether there could be better ways to reach the overall goal of creating a better working environment. There seems to be several reasons for the lack of knowledge about the processes involved in regulating the working environment (...)